An adaptive hypermedia model based on student's lexicon. Issue 4 (10th July 2017) - Salcedo, Pedro; Pinninghoff, M. Angélica; Contreras, Ricardo; Figueroa, Jorge F.
Abstract: This work presents an adaptive hypermedia proposal that focuses on the students' lexicon. An adequate lexicon knowledge affects dramatically in the learning processes in which the students are involved. In general, students manage a lexicon level that allows them to communicate. However, this is not enough for understanding specialized texts covering specific topics. Our proposal takes into account the interconnecting structures present in the lexicon associated to a student profile. More specifically, we propose a set of rules that, based on the student profile, facilitate the selection of the lexicon. We also provide a description of the different instances involved in the complete process.